2021
DOI: 10.1007/s00220-021-03963-w
|View full text |Cite
|
Sign up to set email alerts
|

Trading Locality for Time: Certifiable Randomness from Low-Depth Circuits

Abstract: The generation of certifiable randomness is the most fundamental information-theoretic task that meaningfully separates quantum devices from their classical counterparts. We propose a protocol for exponential certified randomness expansion using a single quantum device. The protocol calls for the device to implement a simple quantum circuit of constant depth on a 2D lattice of qubits. The output of the circuit can be verified classically in linear time, and is guaranteed to contain a polynomial number of certi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…There, the authors proposed a protocol for certifiable random-number generation with constant depth quantum circuits. The first difference with respect to our work is that [CSV21] do not base the soundness of their protocol on the classical intractability of some computational problem, such as LWE. Instead, the protocol assumes that the "prover" generating the randomness is a circuit of sub-logarithmic depth (showing that sub-logarithmic classical circuits would not succeed in this task).…”
Section: Related Workmentioning
confidence: 98%
See 2 more Smart Citations
“…There, the authors proposed a protocol for certifiable random-number generation with constant depth quantum circuits. The first difference with respect to our work is that [CSV21] do not base the soundness of their protocol on the classical intractability of some computational problem, such as LWE. Instead, the protocol assumes that the "prover" generating the randomness is a circuit of sub-logarithmic depth (showing that sub-logarithmic classical circuits would not succeed in this task).…”
Section: Related Workmentioning
confidence: 98%
“…In terms of constant quantum depth constructions, it is interesting to contrast our work to that of [CSV21]. There, the authors proposed a protocol for certifiable random-number generation with constant depth quantum circuits.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several results related to this separation. Coudron, Stark and Vidick [17] and Le Gall [21] showed a similar separation in the average case setting, instead of the worst case setting considered in the original version of [12]: there exists a relation problem such that constant-depth quantum circuits can solve the relation on all inputs, but any O(log n) depth randomized bounded fan-in classical circuits cannot solve it on most inputs with high probability. Bene Watts et al [8] showed that a similar separation holds against classical circuits using unbounded fan-in gates.…”
Section: Introductionmentioning
confidence: 94%
“…Under assumptions such as the non-collapse of the polynomial hierarchy or the hardness of (appropriate versions of) the permanent, strong evidence of the superiority of weak classes of quantum circuits has been obtained from the 2000s [2,3,4,6,12,13,14,18,19,20,33,39]. A recent breakthrough by Bravyi, Gosset and König [10], further strengthened by subsequent works [5,11,17,21], showed an unconditional separation between the computational powers of quantum and classical small-depth circuits by exhibiting a computational task that can be solved by constant-depth quantum circuits but requires logarithmic depth for classical circuits. A major shortcoming, however, is that logarithmic-depth classical computation is a relatively weak complexity class.…”
Section: Introductionmentioning
confidence: 99%